Correlate between Socioeconomic Status with Oxidative Stress in HIV /AIDS Pregnant Women’s - Mishra, Dr. Asha; A. Agnihotri, Dr. Madhuri; Sitholay, Mrs. Pooja; Ratnani, Dr. Rekha (International Journal of Innovative Research in Medical Science, 2018)
Background - Stress during pregnancy can have serious adverse outcomes on the mother, the fetus, newborn, children and even adolescents. Socioeconomic status has been recognized as a predictor of stress amongst pregnant women Aims and Objectives: The aim of the study is to determine the correlation between oxidative stress and socioeconomic status of HIV / AIDs pregnant women. To determine oxidative stress levels we will measure : Glutathione (GSH) concentration Malondialdehyde (MDA) concentration Total Antioxidant Status (TAS) Glutathione Peroxidase (GPx) Super Oxide Dismutase (SOD) To correlate socioeconomic status with oxidative stress in HIV/AIDs pregnant women’s. Result - Shows the level of hormones in normal pregnant women and HIV positive pregnant women. Hormone level in HIV pregnant women were significantly decreased found compare to normal pregnant women. Conclusion: Although the prevalence of HIV in India is low, the lack of strong wealth patterning in the risk of HIV suggests a more generalized distribution of HIV risk than some of India's high-risk group HIV prevention policies have assumed. The positive association between state economic development and individual risk for HIV is intriguing and requires further scrutiny. On the basis of our result we concluded that the HIV positive pregnant women experience more free radical injury than those with HIV negative pregnant women. Due to oxidative stress, when highly induce it is involved in tissue damage. These mechanisms lead to the decrease of the antioxidant capacity of the body in HIV positive pregnant women.